Selection of Transverse Bars in Reinforced Concrete Beams while Ensuring the Minimum Consumption of Reinforcement - Yu. A. Shaposhnikova; V. S. Kuznetsov (Железобетонные конструкции)
The paper considers the influence of various factors on the consumption of transverse reinforcement in the design of sections of linear bending reinforced concrete elements. The aim of the work is to determine the degree of influence of the pitch, diameter and class of transverse rods, as well as other factors, on the minimum consumption of clamps at various levels of loading of a linear bending element. The calculation and analytical method of research was used, based on the results of applying various diameters of transverse rods, reinforcement classes. The object of the study was a beam of rectangular cross section, in which the step of the clamps varied from the minimum to the maximum allowable standards, with a stepwise changing load. Research results. It has been established that the optimal longitudinal single reinforcement of the beam is achieved by applying a maximum force of 255 kN from the studied load range. When a concentrated force of less than 125 kN is applied to the beam, the transverse reinforcement is installed according to the design requirements. The most economical solution for reinforcing a beam with transverse bars is achieved with class A240 and a step of 0.235 m and 0.140 m, with an overrun of 0% and 6.9%, respectively. The use of transverse bars made of A500C class reinforcement, with the accepted beam parameters of 0.3×0.5 m, with single reinforcement, with the application of a force of 255 kN, is not advisable, since the assortment of reinforcing steels does not provide for diameters less than 10 mm. The dependencies and the levels of influence of the use of different pitches, diameters and classes of transverse rods, with a stepwise changing load, on the minimum consumption of transverse reinforcement in the design section of the beam are established. The presented work specifies the consumption of transverse reinforcement for its most economical use.